An Experimental Study of Radiated Energy from an Optical Fiber and the Potential for an Optical MIMO System - Hasan Farahneh; Jamal S. Rahhal; Dia I. Abualnadi; Ibrahim Mansour; Ahmad K. Atieh; Xavier Fernando (Applied Sciences)
Leaky feeders provide seamless and uniform signal coverage in confined spaces like tunnels, mines, and buildings. Their easy scalability and integration with modern systems, like Multiple Input Multiple Output (MIMO), make them ideal for environments requiring reliable and consistent connectivity. However, using optical fiber as a radiating cable has never been investigated before. This may seem infeasible at first sight. However, our experimental study shows otherwise. We measured light leaking from a bent optical fiber transmitter. We also derived closed-form formulas to describe the amount of leakage energy and found that this energy exponentially varies with the square of the curvature radius. This allows us to design an Optical Leaky Feeder (OLF) transmission system for the first time. Then, we analytically show that a slotted optical fiber can be used as a MIMO receiver. The proposed system can ensure reliable, high-quality signal distribution even in challenging environments like tunnels, industrial settings, and dense urban areas.